Early and Late Benefits of Prasugrel in Patients With Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention - Antman, Elliott M.; Wiviott, Stephen D.; Murphy, Sabina A.; Voitk, Juri; Hasin, Yonathan; Widimsky, Petr; Chandna, Harish; Macias, William; McCabe, Carolyn H.; Braunwald, Eugene (Journal of the American College of Cardiology, 2008)
Early and Late Benefits of Prasugrel in Patients With Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention: A TRITON–TIMI 38 (TRial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet InhibitioN with Prasugrel–Thrombolysis In Myocardial Infarction) Analysis Elliott M. Antman, Stephen D. Wiviott, Sabina A. Murphy, Juri Voitk, Yonathan Hasin, Petr Widimsky, Harish Chandna, William Macias, Carolyn H. McCabe, Eugene Braunwald Significant reductions in myocardial infarction, stent thrombosis, and urgent target vessel revascularization were observed with the use of prasugrel both during the first 3 days and from 3 days to the end of TRITON–TIMI 38 (TRial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet InhibitioN with Prasugrel–Thrombolysis In Myocardial Infarction). The excess major bleeding found with the use of prasugrel occurred predominantly during the maintenance phase. Approaches to reduce the relative excess of bleeding with prasugrel should focus on the maintenance dose (e.g., reduction in maintenance dose in previously reported high-risk subgroups such as the elderly and those patients with low body weight). We evaluated the relative contributions of the loading and maintenance doses of prasugrel on events in a TRITON–TIMI 38 (TRial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet InhibitioN with Prasugrel–Thrombolysis In Myocardial Infarction) analysis. Prasugrel is superior to clopidogrel in preventing ischemic events in patients with an acute coronary syndrome who are undergoing percutaneous coronary intervention, but it is associated with an increased risk of major bleeding. Landmark analyses for efficacy, safety, and net clinical benefit were performed from randomization to day 3 and from day 3 to the end of the trial. Significant reductions in ischemic events, including myocardial infarction, stent thrombosis, and urgent target vessel revascularization, were observed with the use of prasugrel both during the first 3 days and from 3 days to the end of the trial. Thrombolysis In Myocardial Infarction major non–coronary artery bypass graft bleeding was similar to clopidogrel during the first 3 days but was significantly greater with the use of prasugrel from 3 days to the end of the study. Net clinical benefit significantly favored prasugrel both early and late in the trial. Both the loading dose and maintenance dose of prasugrel were superior to clopidogrel for the reduction of ischemic events. This result emphasizes the importance of maintaining high levels of inhibition of platelet aggregation via P2Y12 receptor inhibition, not only for the prevention of periprocedural ischemic events but also during long-term follow-up. The excess major bleeding observed with the use of prasugrel occurred predominantly during the maintenance phase. Approaches to reduce the relative excess of bleeding with prasugrel should focus on the maintenance dose (e.g., reduction in maintenance dose in previously reported high-risk subgroups, such as the elderly and those patients with low body weight). (A Comparison of CS-747 and Clopidogrel in Acute Coronary Syndrome Subjects Who Are to Undergo Percutaneous Coronary Intervention; NCT00097591)